Accounting Information Systems For Financial Management In Religious Non-Profit Organizations Of The Church - Sarlin P. Nawa Pau; Maria P. L. Muga; Yemima Eka Christi Windya; Melianus E. Tkela (Green Publisher Indonesia, 2022)
The church is a non-profit religious institution. Good financial management of church religious institutions is needed to improve the quality of service to the congregation. One form of church financial management is to manage financial information in a good accounting information system as a form of church responsibility or accountability in managing the congregation's money. This research was conducted using a qualitative descriptive research method. The type of data source used in this study is qualitative data. Sources of data in this study are primary data and secondary data. The data in this study are primary data and secondary data. The data collection technique in this research is through field studies and literature studies. The results of this study are the accounting information system in the context of managing church finances at the Evangelical Masehi Church in Timor Jemaat Kota Baru Klasis Kupang City is cash receipts and disbursements that carry out financial reporting every week on congregation news, monthly financial reports and conduct congregational congregations to report servants and finances every year. The procedure is still carried out using a computer but still manually. This research then creates an accounting information system for cash receipts and disbursements.